Environmental Security in Belt and Road Initiative Green Development Coalition (BRIGC): A Study of Pakistan, Kenya, and Indonesia - Yohana Valentine; Agus Trihartono; Bagus Sigit Sunarko (Pusbindiklatren Bappenas, 2025)
This study examines the efficacy of the Belt and Road Initiative Green Development Coalition (BRIGC) in balancing China's economic interests with environmental security in BRI partner countries, namely Pakistan, Kenya, and Indonesia. Using a descriptive qualitative and case study approach, the research is based on Barry Buzan's theory of security expansion and the concept of Anthropocentrism. The analysis reveals that, although BRIGC promotes green development, weaknesses in policy enforcement, limited authority, and inability to bind partner countries continue to cause BRI projects produce environmental damage, debt dependency, and threats to human security. In all three countries, BRI projects reflect an anthropocentric development model, where the state’s economic interests take precedence over environmental protection and community welfare. This study concludes that the BRIGC has been unable to fulfill its function as an effective green coalition in promoting sustainable development.